Hippocampal subfield involvement in patients with transient global amnesia: short communication - Wittayer, Matthias Sebastian; Hoyer, Carolin; Roßmanith, Christina; Platten, Michael; Gass, Achim; Szabo, Kristina (Journal of neuroimaging, 2022)
Background and Purpose Transient global amnesia (TGA) is a rare neurological disorder causing a transient disturbance of episodic long-term memory. Its etiology remains yet to be identified; the only consistently reported findings in patients with TGA are small hyperintense lesions in the hippocampus on diffusion-weighted magnetic resonance imaging (DWI). The aim of this study was to define whether these lesions are subfield specific, as suggested previously. Methods High-resolution multiplanar reformation T1 and DWI of the hippocampus were acquired in 25 patients after TGA with a total of 43 hippocampal lesions. Hippocampal subfields were determined using the FreeSurfer software and the location of the DWI lesions was transformed to the T1 images after data co-registration. Additionally, hippocampal subfield volumes in each patient were calculated and compared with that of 20 healthy controls. Results Hippocampal lesions were most frequently detected in the cornu ammonis area 1 (CA1) subfield (30.2%), the hippocampal tail (28.0%), and the subiculum (21.0%); however, lesions were also found in other subfields. There was no significant difference between patients and controls concerning the volumes of the hippocampal subfields. Conclusions Contrasting previous assumptions, we found DWI hyperintense lesions not to be restricted to the CA1 subfield. The visualization of focal hippocampal lesions on diffusion imaging located to several different hippocampal subfields suggests a potential pathophysiology of TGA independent of microstructural hippocampal anatomy and subfield-specific vulnerability.
Erstmals veröffentlicht: 02. Februar 2022
Gesehen am 07.05.2024